CO Multi-line Imaging of Nearby Galaxies (COMING). VI. Radial variations in star formation efficiency. (12th March 2019) - Muraoka, Kazuyuki; Sorai, Kazuo; Miyamoto, Yusuke; Yoda, Moe; Morokuma-Matsui, Kana; Kobayashi, Masato I N; Kuroda, Mayu; Kaneko, Hiroyuki; Kuno, Nario; Takeuchi, Tsutomu T; Nakanishi, Hiroyuki; Watanabe, Yoshimasa; et al.
Abstract: We examined radial variations in molecular-gas based star formation efficiency (SFE), which is defined as star formation rate per unit molecular gas mass, for 80 galaxies selected from the CO Multi-line Imaging of Nearby Galaxies project (Sorai et al. 2019, PASJ, 71, S14). The radial variations in SFE for individual galaxies are typically a factor of 2–3, which suggests that SFE is nearly constant along the galactocentric radius. We found an averaged SFE in 80 galaxies of (1.69 ± 1.1) × 10 −9  yr −1, which is consistent with Leroy et al. (2008, AJ, 136, 2782) if we consider the contribution of helium to the molecular gas mass evaluation and the difference in the assumed initial mass function between the two studies. We compared SFE among different morphological (i.e., SA, SAB, and SB) types, and found that SFE within the inner radii ( r / r 25 < 0.3, where r 25 is the B -band isophotal radius at 25 mag arcsec −2 ) of SB galaxies is slightly higher than that of SA and SAB galaxies. This trend can be partly explained by the dependence of SFE on global stellar mass, which probably relates to the CO-to-H2 conversion factor through the metallicity. For two representative SB galaxies in our sample, NGC 3367 and NGC 7479, the ellipse of r / r 25 = 0.3 seems to cover not only the central region but also the inner part of the disk, mainly the bar. These two galaxies show higher SFE in the bar than in the spiral arms. However, we found an opposite trend in NGC 4303; SFE is lower in the bar than in the spiral arms, which is consistent with earlier studies (e.g., Momose et al. 2010, ApJ, 721, 383). These results suggest a diversity of star formation activities in the bar.